Emotion Marketing: The Hallmark Way of Winning Customers for Life - Robinnette Scott (McGraw -Hill, 2000)
To its millions of loyal customers world-wide, the Hallmark brand stands for more than just greeting cards; it embodies the elusive item every company hopes to capture—the customer’s heart. Hallmark has found that one of the keys to attaining superior customer loyalty is through emotion. Now for the first time, Hallmark reveals its groundbreaking strategy: Emotion Marketing.